Modelo de Semaforización Inteligente para la Ciudad de Bogotá - Salcedo Parra, Octavio José; Pedraza Martínez, Luis Fernando; Hernández Suárez, César Augusto (Ingeniería, 2005)
This article details the design of a traffic system model for vehicles, which examines the traffic traveling through a series traffic lights on a main road in Bogota. The Adaptive Network Based Fuzzy Inference Systems is used to synchronize the time of duration and phase angle of the traffic lights, and also tries to maintain the maximum possible velocity of the vehicles traveling on the road (Figure 1). The model is simulated in Matlab software and the results are evaluated at macroscopic level with the fixed time model currently operating in Bogota.